Ethical Relativism, Environmental Ethics, and Global Environmental Care - Airoboman, Felix Ayemere (NIU Journal of Social Sciences, 2021)
This study analyses the implications, which ethical relativism would have when applied in environmental study and conservation. It examines whether the complex questions raised in environmental ethics and about environmental sustainability at a global scale can be resolved within the context of ethical relativism. It also concurrently inquires whether the challenges posed by the natural environment can be resolved or mitigated within relativist context. The study discusses the nature of ethical relativism and draws attention to the limitations of the standpoint of this theory. Thereafter, it discusses the nature of environmental ethics and its relation to ecological degradation and sustainable environment. It then argues that ethical relativism is a bad marriage in environmental ethics and sustainability, and a bad candidate in resolving the challenges posed by the natural environment, given not only the fact that most environmental problems transcend cultural borders but also that the domestic ones can assume global dimension. By extension, the study exposits the challenges of ineffectiveness faced by relativism in restoration ecology, environmental law and environmental justice. It argues that in the present state of environmental challenges, ethical relativism cannot be relied upon in addressing successfully, issues in environmental ethics and in sustaining the natural environment. To meet the objective of this inquiry, the study raises significant issues about ethical relativism and the environment, and interrogates them stage by stage to enable adequate attention and instantaneous response to the issues raised. The study adopts the conceptual and critical methods of philosophical analyses. Keywords: Culture-dependent morality, Trans-cultural relations, Global environment, Moral chaos, Environmental ethics, Sustainable environment, Cross-cultural environmental ethic, International cooperation